VERY LONG-CHAIN CERAMIDES ARE INCREASED IN SERUM EXOSOMES WITH AGING IN BOTH HUMAN SUBJECTS AND NON-HUMAN PRIMATES. (11th November 2018) - Krishnan, P; Khayrullin, A; Martinez, L; Mendhe, B; Fulzele, S; Liu, Y; Mattison, J A; Hamrick, M W
Abstract: Exosomes are extracellular vesicles that function in cell-to-cell communication through delivery of proteins, lipids, and mRNAs to target cells via endocytosis and membrane fusion. These vesicles are enriched in ceramide, a sphingolipid associated with promotion of cell senescence and apoptosis. We investigated the ceramide profile of serum exosomes from young (24–40 y.o.) and older (75–90 y.o.) women (n=5 per age group) and young (6–10 y.o.) and older (25–30 y.o.) rhesus macaques (n=6 per group). Exosomes were isolated using size-exclusion chromatography. Proteomic analysis was used to validate known exosome markers from Exocarta; nanoparticle tracking analysis (Zetaview) was used to characterize exosome size and concentration, and specific ceramide species were identified with lipidomics. Results show a significant increase in the average amount of C24:1 ceramide in exosomes from older women (15.4 nmole/sample) compared to those from younger women (3.8 nmole/sample). The levels of C24:1 ceramide detected in serum-derived exosomes from older women were almost 10-fold higher than levels of shorter-chain ceramides such as C14, C16, and C20 ceramide. Results were similar in non-human primate serum samples with increased amount of C24:1 ceramide (9.3 nmole/sample) in older monkeys compared to the younger monkeys (1.8 nmole/sample). C24:1 ceramide is implicated in aging and higher levels have been associated with poor cardiovascular health and memory impairment in older adults.